GAYA BAHASA ASONANSI DALAM CATATAN HARIAN CATATAN NAJWA KARYA NAJWA SHIHAB - Firman Tara; Asiho Pama Mailani H (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purpose of the research is to describe the assonance figurative language in Catatan Harian Catatan Najwa by Najwa Shihab. The data of this research is primary data which consists of quotations of assonance figurative language and the metaphor of that assonance. The source of this data is daily notes of Catatan Najwa by Najwa Shihab. This research is qualitative with descriptive method. Through collecting data, choosing data, and analyzing data, the research can understand the assonance figurative language and the metaphor from the daily notes of Catatan Najwa by Najwa Shihab. Moreover, the researcher interpreted it logically and drawed the conclusion for each discussion.The result shows that there are three things that are related to this research, they are two kinds of assonance figurative language; assonance figurative language of vowel repetition on one speech and one line. For example: Indonesia adalah kata kerja, kita semua yang harus menuntaskannya. Next is assonance figurative language with the repetition of vowel pattern on two lines, such as: Cukup lama dia geming membatuMenyindir kekuasaan yang penuh ragu. Moreover, there are some words that comprise metaphor, such as: Uluran tangan which means giving help, geming membatu which means being silent without saying any words, ibu pertiwi which means Indonesia land, which is suitable with this theory (Suwandi, 2011: 117). Thus, it can be concluded that there are two kinds of assonance figurative language and words that have metaphor meaning in Catatan Najwa daily notes.